(untitled) (International Journal of Physiology, 2024)
Objective: This review article aims to compare and analyse the effect of Instrument Assisted soft tissue mobilization and massage on neck pain. Methods: This review analysed two databases i.e. (PubMed, google scholar), and extracted the studies of neck pain. Article published in the English language were included in the studies from 2016 to 2023. 10 studies were included in this review. Outcome measures used neck pain intensity, and neck disability, and secondary outcomes measure were quality of life (QOL), neck range of motion (ROM), visual analogue scale(VAS). Result: Ten studies on 328 patients with neck pain comparing IASTM with Massage were included. Finding of the studies demonstrated that both IASTM and massage treatment were efficient in lowering neck discomfort and enhancing neck range of motion. IASTM showed significant improvement as compared to massage treatment in terms of minimising discomfort and enhancing neck mobility.(p=0.05, p=0.001) Conclusion: It can be inferred from the comparative study of instrument-assisted soft tissue mobilisation (IASTM) and massage on neck pain that both treatments are efficient in easing discomfort and enhancing range of motion in sufferers of neck pain. IASTM was significant to massage in terms of relieving pain and enhancing neck mobility. But it’s crucial to remember that each intervention has its own distinct advantages and could be a better choice for some people depending on their requirements and preferences.